Burning mouth complaints: clinical characteristics of a Brazilian sample (Clinics, 2007)
OBJECTIVE: Evaluation of the clinical characteristics of burning mouth complaints (BMC) in a series of Brazilian patients referred to a large teaching hospital. MATERIALS AND METHODS: 66 patients with burning mouth complaints were evaluated through a standardized protocol. RESULTS: 56 women and 10 men were examined, ranging in age from 35-83 years. The primary location of the complaints was reported to be the tongue. Thirty-six patients reported a precipitating event. The mean VAS pain levels were 7.5 in women and 6.11 in men. The average estradiol levels in women were low (